A systematic review of scientific studies and case reports on music and obsessive-compulsive disorder - Truong, TPA; Applewhite, B; Heiderscheit, A; Himmerich, H (MDPI, 2021)
Obsessive-compulsive disorder (OCD) is a severe psychiatric disorder, which can be associated with music-related symptoms. Music may also be used as an adjunct treatment for OCD. Following the PRISMA guidelines, we performed a systematic literature review exploring the relationship between music and OCD by using three online databases: PubMed, the Web of Science, and PsycINFO. The search terms were “obsessive compulsive disorder”, “OCD”, “music”, and “music therapy”. A total of 27 articles were utilised (n = 650 patients/study participants) and grouped into three categories. The first category comprised case reports of patients with musical obsessions in patients with OCD. Most patients were treated with selective serotonin reuptake inhibitors (SSRIs) or a combination of an SSRI and another pharmacological or a non-pharmacological treatment, with variable success. Studies on the music perception of people with OCD or obsessive-compulsive personality traits represented the second category. People with OCD or obsessive-compulsive personality traits seem to be more sensitive to tense music and were found to have an increased desire for harmony in music. Three small studies on music therapy in people with OCD constituted the third category. These studies suggest that patients with OCD might benefit from music therapy, which includes listening to music.